Que autoridades sustentam a autoridade? a argumentatividade no gênero artigo científico através do arrazoado por autoridade e da modalização discursiva - Bessa, Clécida Maria Bezerra Bessa (2015)
This study, carried out with analysis of scientific papers, written by researchers and published in journals, tries to investigate how the linguistic-discursive functioning of modalization and polyphony of speakers, more specifically of the arguments from authority, in the academic genre scientific paper occurs, as elements indicating subjectivity (argumentativeness). Besides, we also aim at investigating how these phenomena contribute to characterize the linguistic style of the genre which is being studied here. We assert that this investigation is descriptive and interpretativist and has the theoretical-methodological principles of Argumentative Semantics as a general guidance. Therefore, the fundamentals of this work is the Theory of Argumentation in Language by Ducrot and collaborators (1987, 1988, 1994), with increments and reformulation proposed by Espíndola ( 2004) and Nascimento (2005, 2009, 2014). We base our studies on the phenomenon called discursive modalization (CASTILHO E CASTILHO, 1993; CERVONI, 1989; GARCIA NEGRONI, 2008, 2011; NASCIMENTO, 2005, 2009, 2014; NASCIMENTO E SILVA, 2012; among others); as well as on the conception of discursive genres (BAKHTIN, 2000). The corpus is composed by twenty (20) scientific papers, collected from journals recognized by CAPES, with its qualis labels A and B. Four (4) scientific papers of each area of knowledge are analyzed. The areas of knowledge are the following: Human Sciences (Education); Social Sciences (Communication); Exact and Earth Sciences (Statistics); Engineering (Chemical Engineering); Health Sciences (Food and Nutrition). The results point that scientific papers are discourses full of subjectivities and are also discursive-oriented, in which voices echo either explicitly or implicitly, in other words, they are part of a genre where polyphony and modalization are present meaningfully. The responsible speaker for a scientific paper makes use of arguments from authority and of discursive modalization as a way to highlight argumentativeness within the enunciated and to orient how one wishes his/her interlocutor to read/comprehend the voices of authorities bought to compose the text.